New risks and opportunities for food security: Scenario analyses for 2015 and 2050 - von Braun, Joachim; Rosegrant, Mark W.; Pandya-Lorch, Rajul; Cohen, Marc J.; Cline, Sarah A.; Brown, Mary Ashby; Bos, Maria Soledad (International Food Policy Research Institute, 2005)
Given the number of undernourished people in the developing world and the increasingly complex risks to food security, policymakers are faced with an enormous agenda. Freeing people from hunger will require more and better-targeted investments, innovations, and policy actions, driven by a keen understanding of the dynamic risks and forces that shape the factors affecting people’s access to food and the links with nutrition. The International Food Policy Research Institute’s (IFPRI’s) International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) provides insight into the management of these risks through appropriate policy actions. By projecting future global food scenarios to 2050, IMPACT explores the potential implications of policy action and inaction in several main risk areas as well as the effects on child malnutrition in the developing world, commodity prices, demand, cereal yields, production, and net trade. In the progressive policy actions scenario, which assumes increased investment in rural development, health, education, and agricultural research and development, developing country governments and the international community are able to dramatically reduce the number of food-insecure people, leading to a worldwide decline in hunger. Under these conditions, Latin America and China are able to virtually eliminate child malnutrition by 2050. Bolstered by the development and dissemination of improved technologies and better infrastructure, crop production and yields increase in developing countries. Notably, the bulk of the growth in production is driven by yield increases rather than by expanding land area. Spurred by growth in the agricultural sector, average incomes in developing countries increase. Rising incomes bolster demand for high-value agricultural products, such as meat, dairy, and fruits and vegetables; global livestock production more than doubles, for example. Average per capita calorie supplies for developing countries exceed 3,400 per day, well in excess of minimum requirements. The policy failure scenario assumes greater political discord and more extensive agricultural protectionism, together with the failure of policies to deal with food emergencies related to conflict. Slow growth and trade restrictions lead to stagnation in average per capita calorie availability, which remains only slightly above minimum requirements until after 2030, when availability increases. In addition, crucial investments in agriculture, rural development, and poverty reduction are forgone or displaced. Because of limited investment in agricultural research and technology, this scenario has a high level of crop area expansion as a result of relatively rapid population growth and slim yield improvements in developing countries. This scenario also results in flat maize prices, declining per capita cereal demand, falling beef prices, and relatively flat meat demand. As a result of the policies in this scenario, the number of malnourished children in developing countries rises between 1997 and 2015, after which there are only modest declines. In the technology and natural resource management failure scenario, yield growth falls even more than under the preceding scenario, forcing farmers to move into marginal producing areas, which causes a more rapid expansion of cereal area into less productive land that does not compensate for the yield shortfalls (and causes environmental degradation). As a result, cereal prices rise substantially through 2030 and then fall off only gradually. Beef and other meat prices, which are affected by the price of feed, follow a similar pattern. Developing-country per capita calorie availability is essentially unchanged over 1997–2050 and remains at a barely adequate average level. Given unequal access to the food that is available, millions of people actually consume less than the minimum. The occurrence of child undernourishment is even higher than under the policy failure scenario in all developing-country regions. Overall, the technology and natural resource management failure scenario results in the worst impact on food security and child malnourishment in the developing world. The progressive policy scenario outlines several of the most crucial positive steps. National governments and the international community must assume a new focus on agricultural growth and rural development, along with increasing their investments in education, social services, and health. Policies to encourage synergistic growth in the nonfarm sectors are also needed to spur broad-based economic growth. Underpinning these strategies and research agendas must be a firm commitment to reducing hunger and improving the welfare of the world’s undernourished people.